1993
DOI: 10.1111/j.1365-2141.1993.tb08280.x
|View full text |Cite
|
Sign up to set email alerts
|

UVB radiation exposes fibrinogen binding sites on platelets by activating protein kinase C via reactive oxygen species

Abstract: Previous studies have shown that ultraviolet B (UVB) radiation causes platelet aggregation by exposing fibrinogen binding sites via activation of an intracellular mechanism. In the present study we have further investigated the routes of platelet activation following UVB exposure. Evidence is provided that UVB radiation does not activate the platelets via the classical Phospholipase A2 and Phospholipase C routes. Despite this observation, UVB-induced fibrinogen binding was found to be correlated with a 40% inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…Van Marwijk and colleagues observed that UV-B irradiation resulted in increased fibrinogen binding to platelets. 9 Furthermore, the UV-B-induced aggregation appeared to be dependent on PKC activation, signifying an important role for platelet signaling in UV-B-mediated activation of integrin ␣IIb␤3, the receptor binding fibrinogen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Marwijk and colleagues observed that UV-B irradiation resulted in increased fibrinogen binding to platelets. 9 Furthermore, the UV-B-induced aggregation appeared to be dependent on PKC activation, signifying an important role for platelet signaling in UV-B-mediated activation of integrin ␣IIb␤3, the receptor binding fibrinogen.…”
Section: Introductionmentioning
confidence: 99%
“…Van Marwijk and colleagues observed that UV-B irradiation resulted in increased fibrinogen binding to platelets. 9 Furthermore, the UV-B-induced aggregation appeared to be dependent on PKC activation, signifying an important role for platelet signaling in UV-B-mediated activation of integrin ␣IIb␤3, the receptor binding fibrinogen.As a member of the integrin family, ␣IIb␤3 consists of a large type I transmembrane ␣/␤ heterodimer, which is capable of bidirectional signaling through the plasma membrane. On unstimulated platelets, ␣IIb␤3 resides in an inactive conformation on the plasma membrane, but it is rapidly switched to an "on" state when the platelet becomes activated after stimulation with agonists such as thrombin, collagen, or adenosine diphosphate (ADP).…”
mentioning
confidence: 99%
“…Interestingly, the link between UVB-ROS-phosphorylation and platelet activation was suggested by Van Marwijk Kooy et al in 1993 [110]. They observed that after UVB illumination of platelets, there was increased fibrinogen binding that correlated with a 40% higher level of phosphorylation downstream of protein kinase C. UV-induced phosphorylation and platelet aggregation were significantly reduced in the presence of SOD and catalase, respectively, which are scavengers of O 2 −· and H 2 O 2 .…”
Section: Ros-phosphorylation Crosstalkmentioning
confidence: 99%
“…In contrast to UVCtreated platelet units which are intended to be irradiated just after preparation and then be stored until transfusion, UVB irradiation of platelets was always performed shortly before transfusion. Van Marwijk and colleagues [41] observed that irradiation of platelets with UVB light results in exposure of fibrinogen binding sites and subsequent platelet aggregation. Another group found an increase in the expression of activation in platelets over time and a reduced post-transfusion recovery of UVB-treated platelets in a dose-dependent manner [42].…”
Section: In Vitro Qualitymentioning
confidence: 99%